2018
DOI: 10.1016/j.apcatb.2017.10.066
|View full text |Cite
|
Sign up to set email alerts
|

Zirconia-supported tungstophosphoric heteropolyacid as heterogeneous acid catalyst for biodiesel production

Abstract: Highlights  Sol-gel/Hidrothermal method is efficient for the immobilization of HPA on zirconia  The presence of the HPA leads to significant modifications on zirconia  Supported HPA on zirconia are suitable catalysts for esterification.  Leaching and the porosity blockage cause a reduction of the catalytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(48 citation statements)
references
References 48 publications
2
45
0
1
Order By: Relevance
“…The zirconia support was generated by hydrolysis of an alkoxyde precursor in the presence of the heteropolyacid, which led to materials with homogeneously well-dispersed clusters, as well as to an increasing contribution of the tetragonal ZrO 2 crystalline phase. A sample with a 30% mass percentage of heteropolyacid was identified as the most efficient catalyst because it afforded conversions above 90% and showed lower loss of activity over successive reaction runs among the studied materials [74].…”
Section: Zro 2 -Based Catalystsmentioning
confidence: 99%
“…The zirconia support was generated by hydrolysis of an alkoxyde precursor in the presence of the heteropolyacid, which led to materials with homogeneously well-dispersed clusters, as well as to an increasing contribution of the tetragonal ZrO 2 crystalline phase. A sample with a 30% mass percentage of heteropolyacid was identified as the most efficient catalyst because it afforded conversions above 90% and showed lower loss of activity over successive reaction runs among the studied materials [74].…”
Section: Zro 2 -Based Catalystsmentioning
confidence: 99%
“…The numerous disadvantages of homogenous base and acid catalysts, such as soap formation, catalyst recovery, high corrosion, and inhibition by water [1,24] can be replaced using heterogeneous catalysts such as alkaline [25] and alkaline earth metal oxides [2,26,27], mixed oxides [28][29][30], modified layered double hydroxides [31][32][33][34], zeolites [35][36][37], sulfonated solids [38], ion exchange resins [39][40][41], supported heteropolyacids [42,43], etc. In order to design new catalysts based on the modern concept of environmental protection, greatest attention of many scientists is directed at investigation of different waste materials (fly ash from coal-fired power stations (CFPSs), biomass fly ash, agricultural and animal waste, industrial waste reach in calcium such as mud and slug, and natural sources) for potential catalyst synthesis, which can often be very dangerous and leave a lasting impact on the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, not only its catalytic activity and selectivity were improved, but also the product was easy to separate, and the catalyst was easily regenerated, the production process was simplified. There are many works studying polyoxometalate on a variety of supports (Hanif et al, 2017 ; Alcañiz-Monge et al, 2018 ; Yuan et al, 2020 ), the research on surface properties showed that supporting polyoxometalate firmly on the support was key (Hu et al, 1995 ). Activated carbon not only has high specific surface area and large pore size but also can be adjusted as needed; it was a good catalyst support.…”
Section: Introductionmentioning
confidence: 99%